VONIS BEBAS TINDAK PIDANA PENCABULAN ANAK KANDUNG DITINJAU DARI PUTUSAN NOMOR 36/PID.SUS/2023/PN LBB - Shodiq, Muhammad Jafar; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: The presence of children in a family brings both happiness and a great responsibility for parents to protect them from various forms of violence, including sexual abuse. In practice, in the ruling No. 36/PID.SUS/2023/PN/LBB, the judge issued an acquittal for Budi Satria in a case of sexual violence against his own child. This clearly reflects the weak implementation of the Child Protection Law and the urgent need to strengthen law enforcement, especially in cases lacking witnesses and evidence. This study aims to analyze the legality and effectiveness of child protection law enforcement using a normative juridical approach. The research adopts a normative juridical method focusing on the implementation of Law Number 35 of 2014 on Child Protection, particularly in cases of sexual violence committed by biological fathers. The study is descriptive-analytical, employing qualitative data analysis through the review of legal regulations, court decisions, and relevant literature. The findings reveal that legal protection for child victims of sexual violence, particularly when the perpetrator is a parent, faces significant challenges due to gaps in legal application and evidence gathering. The acquittal in the case of child molestation underscores the need to strengthen law enforcement, child protection, and comprehensive efforts to prevent violence through the active involvement of all stakeholders. Collective efforts from the government, non-governmental organizations, and the community are necessary to create a safe and supportive environment for children to grow and thrive, free from the threat of sexual violence.Keywords: Judge’s consideration, Free verdict, Sexual violence, Biological children, Child protection.